Preparation method and application of WO3-FeVO4 gas-sensitive material
By preparing WO3-FeVO4 gas-sensitive material, using n-n heterojunction structure to enhance electron transport and reactivity, the problem of high working temperature for NO2 gas detection in the prior art is solved, and the detection effect of high sensitivity and low operating temperature is achieved.
Patent Information
- Application Number
- CN202411425719.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-14
Smart Images

Figure CN118937423B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas-sensitive materials, and specifically relates to a preparation method of a WO3-FeVO4 gas-sensitive material and application thereof. Background Art
[0002] NO2 is a gas with a strong pungent odor. It can not only form acid rain and cause environmental damage, but also cause potential harm to the respiratory systems of humans and animals. Therefore, it is necessary to develop highly sensitive, low-cost, and maintenance-free NO2 monitoring technology. Currently, gas sensors are the most convenient way to detect these gases. In order to explore gas sensors, high-performance gas-sensitive materials must be developed.
[0003] In the field of gas sensing, WO3 as an n-type semiconductor sensor has good chemical stability and sensitivity, and can detect toxic oxidizing and reducing gases in the environment at low cost; however, in application, gas sensors need to have the characteristics of high sensitivity and low operating temperature, and a single metal oxide semiconductor is difficult to meet the above requirements; Chinese patent document with publication number CN202310319394 discloses a method for detecting trimethylamine gas using WO3 / SnO2 gas-sensitive material. The invention uses a two-step hydrothermal method to prepare a WO3 / SnO2 composite sensitive material, and uses the heterogeneous structure formed between WO3 and SnO2 to improve the detection ability of trimethylamine gas. When the operating temperature is 250°C, the sensitivity of trimethylamine gas with a concentration of 10ppm reaches 14.4. Although a relatively high sensitivity is obtained, the operating temperature is relatively high, and it is difficult to achieve industrial production. Summary of the invention
[0004] The purpose of the present invention is to provide a WO3-FeVO4 gas-sensitive material. By preparing a nn heterojunction, the electron transmission efficiency and surface reaction active sites of the gas-sensitive material can be enhanced, and the reaction of gas molecules on the surface of the gas-sensitive material can be enhanced, thereby improving the overall performance of the gas-sensitive material.
[0005] In order to solve the above problems, the present invention adopts the following technical solutions:
[0006] The invention provides a WO3-FeVO4 gas-sensitive material, comprising nanorod-shaped WO3 and nanoparticle-shaped FeVO4 attached thereto; the nanoparticle-shaped FeVO4 and the nanorod-shaped WO3 present a nn heterostructure; and the molar ratio of the nanoparticle-shaped FeVO4 to the nanorod-shaped WO3 is 1:5-16.
[0007] Preferably, the molar ratio of nano-particle FeVO4 to nano-rod WO3 is 1:11.
[0008] The present invention provides a method for preparing the above-mentioned WO3-FeVO4 gas-sensitive material, comprising the following steps:
[0009] S1. Na2WO4·2H2O and NaCl were dissolved in deionized water, concentrated hydrochloric acid was added to adjust the pH, the mixture was stirred continuously, a hydrothermal reaction was performed, and the precipitate was centrifuged and dried to obtain a nanorod-shaped WO3 gas-sensitive material;
[0010] S2. Dissolve the nanorod-shaped WO3 gas-sensitive material in deionized water to obtain solution A; dissolve NH4VO3 and Fe(NO3)3·9H2O in deionized water to obtain solution B; slowly pour solution B into solution A to carry out a hydrothermal reaction, centrifuge, dry and calcine the precipitate to obtain WO3-FeVO4 gas-sensitive material.
[0011] Preferably, in step S1, the molar ratio of Na2WO4·2H2O to NaCl is 1:4-6; the pH value is adjusted to 1-2; the continuous stirring time is 3-5 hours; the hydrothermal temperature is 160-180°C, and the hydrothermal time is 20-24 hours; the drying temperature is 60-80°C, and the time is 8-12 hours.
[0012] Preferably, in step S2, the molar ratio of NH4VO3, Fe(NO3)3·9H2O and nanorod-shaped WO3 gas-sensitive material is 1:1:5-16; the hydrothermal temperature is 160-200°C, and the hydrothermal time is 4-6 hours; the drying temperature is 60-80°C, and the time is 8-12 hours; the calcination temperature is 400-600°C, and the calcination time is 2-4 hours.
[0013] The present invention also provides a technical solution for using WO3-FeVO4 gas-sensitive material for NO2 gas detection. Beneficial Effects
[0014] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0015] (1) The WO3-FeVO4 gas-sensitive material provided by the present invention has nanorod-shaped WO3 with good electrical conductivity and a large specific surface area, which enhances the electrical conductivity of the WO3-FeVO4 gas-sensitive material and provides more active sites for the adsorption of NO2 gas molecules on the surface of the material; the unique electronic structure of nanoparticle-shaped FeVO4 can promote electron transfer to enhance the gas reaction on the surface of the WO3-FeVO4 gas-sensitive material, thereby improving the responsiveness of the WO3-FeVO4 gas-sensitive material to NO2 gas.
[0016] (2) The WO3-FeVO4 gas-sensitive material provided by the present invention, the nn heterojunction synthesized by nanorod-shaped WO3 and nanoparticle-shaped FeVO4, can promote the flow of carriers on the contact surface of the two materials, improve the separation ability of holes and electrons, and enhance the electron transmission efficiency, thereby reducing the working temperature of the WO3-FeVO4 gas-sensitive material for NO2 gas detection.
[0017] (3) The WO3-FeVO4 gas-sensitive material provided by the present invention has a strong adsorption capacity of nano-granular FeVO4 for NO2 gas, and the nn heterojunction synthesized by nanorod-shaped WO3 and nano-granular FeVO4 enhances the electron transmission capacity, thereby promoting the surface NO2 gas reaction of the WO3-FeVO4 gas-sensitive material and enhancing the selectivity of the WO3-FeVO4 gas-sensitive material, so that the response of the WO3-FeVO4 gas-sensitive material to NO2 gas is much greater than that to other gases.
[0018] (4) The preparation method of WO3-FeVO4 gas-sensitive material provided by the present invention adopts a hydrothermal method to synthesize nanorod-shaped WO3 and WO3-FeVO4 gas-sensitive materials in one step. The preparation method is simple, green and environmentally friendly, and easy to industrialize.
[0019] (5) The WO3-FeVO4 gas-sensitive material provided by the present invention can respond to 5ppm NO2 gas at 117°C up to 38.7, and has excellent selectivity and strong anti-interference ability, and has great market development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the SEM image of the synthetic sample of Example 3;
[0021] Figure 2 The XRD spectrum of the sample synthesized in Example 3;
[0022] Figure 3 The selectivity performance diagram of the gas sensors prepared in Comparative Example 1 and Example 3 for NO2 gas;
[0023] Figure 4 2 is an operating temperature diagram of the NO2 sensors prepared in Comparative Example 1 and Example 3. DETAILED DESCRIPTION
[0024] The present invention is described in detail below in conjunction with the embodiments and comparative examples, but the present invention is not limited thereto. The numerical values in the synthetic samples in the embodiments and comparative examples all represent the content of the substance, for example: 11WO3-FeVO4 means that the molar ratio of WO3 to FeVO4 is 11:1, and so on. Example 1
[0025] (1) 6.4 mmol of Na2WO4·2H2O and 32.0 mmol of NaCl were dissolved in 50 mL of deionized water. After complete dissolution, concentrated hydrochloric acid was added to adjust the pH to 1.0. After continuous stirring for 4 h, a hydrothermal reaction was carried out at 180 °C for 24 h. The precipitate was centrifuged and dried at 60 °C for 12 h to obtain a nanorod-shaped WO3 gas-sensitive material.
[0026] (2) 5.0 mmol of WO3 was dissolved in 50 ml of deionized water, which was recorded as solution A. Meanwhile, 1.0 mmol of NH4VO3 and 1.0 mmol of Fe(NO3)3·9H2O were dissolved in 30 ml of deionized water, which was recorded as solution B. Solution B was then slowly poured into solution A, followed by a hydrothermal reaction at 180°C for 5 h. The precipitate was centrifuged, dried at 60°C for 12 h, and finally calcined at 500°C for 3 h to obtain a WO3-FeVO4 gas-sensitive material. The gas-sensitive material obtained in this embodiment was recorded as 5WO3-FeVO4 gas-sensitive material, and this method was also used in the following embodiments. Example 2
[0027] (1) 12.8 mmol of Na2WO4·2H2O and 51.2 mmol of NaCl were dissolved in 50 mL of deionized water. After complete dissolution, concentrated hydrochloric acid was added to adjust the pH to 1.0. After continuous stirring for 3 h, a hydrothermal reaction was carried out at 170 °C for 23 h. The precipitate was centrifuged and dried at 80 °C for 10 h to obtain a nanorod-shaped WO3 gas-sensitive material.
[0028] (2) Dissolve 7.0 mmol of WO3 gas-sensitive material in 50 ml of deionized water, recorded as solution A; at the same time, dissolve 1.0 mmol of NH4VO3 and 1.0 mmol of Fe(NO3)3·9H2O in 30 ml of deionized water, recorded as solution B; then slowly pour solution B into solution A, and then carry out hydrothermal reaction at 160 °C for 6 h, centrifuge the precipitate, dry it at 80 °C for 10 h, and finally calcine it at 400 °C for 4 h to obtain 7WO3-FeVO4 gas-sensitive material. Example 3
[0029] (1) 12.8 mmol of Na2WO4·2H2O and 76.8 mmol of NaCl were dissolved in 50 mL of deionized water. After complete dissolution, concentrated hydrochloric acid was added to adjust the pH to 2.0. After continuous stirring for 5 h, a hydrothermal reaction was carried out at 160 °C for 24 h. The precipitate was centrifuged and dried at 70 °C for 8 h to obtain a nanorod-shaped WO3 gas-sensitive material.
[0030] (2) Dissolve 11mmol of WO3 gas-sensitive material in 50ml of deionized water, recorded as solution A; at the same time, dissolve 1.0mmol of NH4VO3 and 1.0mmol of Fe(NO3)3·9H2O in 30ml of deionized water, recorded as solution B; then slowly pour solution B into solution A, and then carry out hydrothermal reaction at 160℃ for 6h, centrifuge the precipitate, dry it at 70℃ for 8h, and finally calcine it at 400℃ for 4h to obtain 11WO3-FeVO4 gas-sensitive material. Example 4
[0031] (1) 19.2 mmol of Na2WO4·2H2O and 96.0 mmol of NaCl were dissolved in 50 mL of deionized water. After complete dissolution, concentrated hydrochloric acid was added to adjust the pH to 2.0. After continuous stirring for 4 h, a hydrothermal reaction was carried out at 170 °C for 24 h. The precipitate was centrifuged and dried at 80 °C for 8 h to obtain a nanorod-shaped WO3 gas-sensitive material.
[0032] (2) Dissolve 13 mmol of WO3 gas-sensitive material in 50 ml of deionized water, recorded as solution A; at the same time, dissolve 1.0 mmol of NH4VO3 and 1.0 mmol of Fe(NO3)3·9H2O in 30 ml of deionized water, recorded as solution B; then slowly pour solution B into solution A, and then carry out hydrothermal reaction at 200 °C for 4 h, centrifuge the precipitate, dry it at 80 °C for 8 h, and finally calcine it at 600 °C for 2 h to obtain 13WO3-FeVO4 gas-sensitive material. Example 5
[0033] (1) 19.2 mmol of Na2WO4·2H2O and 76.8 mmol of NaCl were dissolved in 50 mL of deionized water. After complete dissolution, concentrated hydrochloric acid was added to adjust the pH to 1.0. After continuous stirring for 5 h, a hydrothermal reaction was carried out at 180 °C for 20 h. The precipitate was centrifuged and dried at 70 °C for 8 h to obtain a nanorod-shaped WO3 gas-sensitive material.
[0034] (2) Dissolve 16 mmol of WO3 gas-sensitive material in 50 ml of deionized water, recorded as solution A; at the same time, dissolve 1.0 mmol of NH4VO3 and 1.0 mmol of Fe(NO3)3·9H2O in 30 ml of deionized water, recorded as solution B; then slowly pour solution B into solution A, and then carry out hydrothermal reaction at 200 °C for 4 h, centrifuge the precipitate, dry it at 70 °C for 8 h, and finally calcine it at 600 °C for 2 h to obtain 16WO3-FeVO4 gas-sensitive material. Example 6
[0035] The samples synthesized in Examples 1-5 are mixed and ground into a moderately viscous liquid in a molar ratio of 2 to 5:1 between the sample and anhydrous ethanol, and the liquid is evenly applied on the sensor device, and the gold electrodes of the sensor device are respectively welded to the base, and then the nickel-chromium resistance wire is assembled on the base, and aged at 80°C to 100°C for 2 to 5 days to obtain a NO2 sensor. Comparative Example 1
[0036] 6.4 mmol of Na2WO4·2H2O and 32.0 mmol of NaCl were dissolved in 50 mL of deionized water. After complete dissolution, concentrated hydrochloric acid was added to adjust the pH to 1.0. After continuous stirring for 4 hours, a hydrothermal reaction was carried out at 180°C for 24 hours. The precipitate was centrifuged and dried at 60°C for 12 hours to obtain a nanorod-shaped WO3 gas-sensitive material. Comparative Example 2
[0037] The sample synthesized in Comparative Example 1 and anhydrous ethanol are mixed in a molar ratio of 2 to 5:1 and ground into a moderately viscous liquid, and then evenly applied on the sensor device, and the gold electrodes of the sensor device are respectively welded to the base, and then the nickel-chromium resistance wire is assembled on the base, and aged at 80°C to 100°C for 2 to 5 days to obtain a NO2 sensor.
[0038] Figure 1 The WO3-FeVO4 gas-sensitive material prepared in Example 3 has the morphology of nanorod-shaped WO3 and nanogranular FeVO4 attached thereto. The diameter of the nanorod-shaped WO3 is in the range of 30 to 80 nm, and the length is in the range of 500 to 2000 nm. The diameter of the nanogranular FeVO4 is in the range of 50 to 150 nm, and the nanogranular FeVO4 is attached to the nanorod-shaped WO3. Compared with the WO3-FeVO4 gas-sensitive material prepared in Example 3, the WO3 prepared in Comparative Example 1 has a unique electronic structure of nanoparticulate FeVO4 and a strong adsorption capacity for NO2 gas, which can promote electron transfer and enhance the gas reaction on the surface of the WO3-FeVO4 gas-sensitive material. At the same time, the preparation of nn heterojunction in the WO3-FeVO4 gas-sensitive material not only improves the conductivity of the material and enhances the electron transfer efficiency, but also promotes the transfer between electrons and holes and provides more active sites, thereby improving the gas-sensitive performance of the WO3-FeVO4 gas-sensitive material to NO2 gas.
[0039] Figure 2The XRD spectrum of the sample prepared in Example 3 shows that the monoclinic WO3 (JCPDS43-1035) phase has a large diffraction intensity on the (002), (020) and (200) crystal planes. The XRD spectrum of the triclinic FeVO4 (JCPDS71-1592) shows that the peak position of FeVO4 in WO3-FeVO4 prepared in Example 3 is consistent. In addition, no other diffraction peaks were observed, confirming the phase purity of all the composites. 11WO3-FeVO4 gas-sensitive material has the characteristic diffraction peaks of WO3 phase, indicating that the original crystal structure of WO3 is not destroyed after FeVO4 modification.
[0040] By testing the response ability of each gas sensor to NO2 gas, the test results are shown in Table 1. By comparing the gas-sensitive responses of WO3-FeVO4 in different proportions in Examples 1-5 with the WO3 gas-sensitive material prepared in Comparative Example 1, it is found that the gas-sensitive response value of 11WO3-FeVO4 gas-sensitive material is as high as 38.7, which is 2.29 times that of WO3 gas-sensitive material, and is significantly higher than other composite ratios. This shows that the nano-granular FeVO4 is attached to the nano-rod-shaped WO3, providing more active sites for NO2 gas molecules to adsorb on the surface of the material, thereby promoting the reaction on the surface of the material. The preparation of the nn heterojunction improves the separation ability of holes and electrons in the gas-sensitive material, thereby improving the response ability of the WO3-FeVO4 gas-sensitive material to NO2 gas.
[0041]
[0042] like Figure 3 As shown, in order to test the selectivity of the gas sensor, at 117°C, 5ppm NO2 gas and 25ppm of other gases were injected respectively. The test found that at the operating temperature of 117°C, the gas-sensitive response value of 11WO3-FeVO4 gas-sensitive material to 5ppm NO2 gas was significantly improved compared with 25ppm of other gases, which shows that 11WO3-FeVO4 gas-sensitive material has excellent selectivity for NO2 gas.
[0043] like Figure 4 As shown in the figure, the response of different materials to a certain concentration of NO2 gas at different temperatures was studied. Among them, the optimal temperature for the WO3 gas-sensitive material to respond to NO2 gas is 121°C, while the temperature corresponding to the highest response of the 11WO3-FeVO4 gas-sensitive material is 117°C, which is significantly lower than the operating temperature of the WO3 gas-sensitive material. This shows that the composite of the two gas-sensitive materials WO3 and FeVO4 improves the response value to NO2 gas at the working temperature, reduces the operating temperature, and greatly improves the gas-sensitive performance of the material to NO2 gas.
Claims
1. Application of WO3-FeVO4 gas-sensitive material in NO2 gas detection, characterized in that: The WO3-FeVO4 gas-sensitive material includes nanorod-shaped WO3 and nano-granular FeVO4 attached thereto; the nano-granular FeVO4 and nano-rod-shaped WO3 present a nn heterostructure; the molar ratio of the nano-granular FeVO4 to the nano-rod-shaped WO3 is 1:11, the diameter of the nano-granular FeVO4 is 50-150nm, the diameter of the nano-rod-shaped WO3 is 30~80nm, and the length is 500~2000nm.
2. The use of a WO3-FeVO4 gas-sensitive material in NO2 gas detection according to claim 1, characterized in that: The preparation method of the WO3-FeVO4 gas-sensitive material comprises the following steps: S1. Dissolve Na2WO4·2H2O and NaCl in deionized water, add concentrated hydrochloric acid to adjust the pH, stir continuously, perform hydrothermal reaction, centrifuge and dry the precipitate to obtain nanorod-shaped WO3 gas-sensitive material, wherein the hydrothermal reaction temperature is 160-180°C and the time is 20-24h; S2. Dissolve the nanorod-shaped WO3 gas-sensitive material in deionized water to obtain solution A; dissolve NH4VO3 and Fe(NO3)3·9H2O in deionized water to obtain solution B; slowly pour solution B into solution A to carry out a hydrothermal reaction, centrifuge, dry and calcine the precipitate to obtain WO3-FeVO4 gas-sensitive material.
3. The use of a WO3-FeVO4 gas-sensitive material in NO2 gas detection according to claim 2, characterized in that: Adjust the pH value to 1-2; the continuous stirring time is 3-5 hours; the drying temperature is 60-80°C and the time is 8-12 hours.
4. The use of a WO3-FeVO4 gas-sensitive material in NO2 gas detection according to claim 2, characterized in that: The hydrothermal reaction temperature is 160-200°C, and the time is 4-6 hours; the drying temperature is 60-80°C, and the time is 8-12 hours; and the calcination temperature is 400-600°C, and the time is 2-4 hours.
Citation Information
Patent Citations
Method for detecting trimethylamine gas by using SnO2-WO3 gas-sensitive material
CN116448819A